Preparation and Evaluation of Ceramic Materials in Wastewater Treatment - Al-Zuhairy, Mudhaffar S; Merzah, Amal S; Zinad, Raghad S (Al-Nahrain Journal of Science, 2018)
Prior to discharge to the environment, domestic wastewater must generally contain not greater than trace levels of various contaminants. This study was conducted touse of naturally avialable ceramic raw materials, without harmful effects on the environment or human and the wastewater brought from Al_Rustamia Location in Baghdad. The efficiency was calculated by evaluating Total Suspended Solid(TSS), Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD5), Phosphat (PO4), and Nitrite (NO3). The wastewater treatment done by using pellet filter , six successful manufactured media and the treatment achieved by three stages , one day, five days and ten days. The unit operation of the treatment system done by two ways aerated system with media, and the second aeration without using ceramic media where that treatment with ceramic media with aeration was better than the treatment with aeration only. The results of treatment of ceramic media with aeration show that the two mixtures gives better removal efficiency of the contimanate materials. These mixtures are mix number (3) and mix number (12).The parameters that indicates the removal efficiency for mix number (3) in the first day were (TSS 68%), (BOD576%), (COD 83%), (PO496%) and (NO394%). The mixtures number (12) was (TSS 78%), (BOD580%), (COD 96%) and (NO398%).The removal efficiency for wastewater quality parameter using aeration without media was (TSS 70%), (BOD520%), (COD 77%), (PO482%), and (NO3100%). The removal for mix number (3) after five days of treatment was (TSS 86%), (BODS 91%),(COD 85%), (PO4 94%) and for (NO3 81%).For mix number (12) the removal efficiency was (TSS ,89%),(BOD5 93%),(COD 85%),(PO494%) and (NO3 78%). Aeration only gives removal efficiency as (TSS 78%),(BOD5 86%),(COD 80%),(PO4 96%) and (NO374%). After ten days of treatment mix number (3) the removal was (TSS 80%), (BOD590%), (COD 76%), (PO496%) and (NO380%). While the results for mix number (12) was (TSS 84%), (BOD595%), (COD 81%), (PO492%) and (NO380%). The removal efficiency for wastewater quality parameters by aeration only was (TSS 69%), (BOD592%), (COD 73%), (PO468%) and (NO377%).